Filamin A is required for vimentin-mediated cell adhesion and spreading - Kim, Hugh (Am J Physiol Cell Physiol, 2010)
Cell adhesion and spreading are regulated by complex interactions involving the cytoskeleton and extracellular matrix proteins. We examined the interaction of the intermediate filament protein vimentin with the actin cross-linking protein filamin A in regulation of spreading in HEK-293 and 3T3 cells. Filamin A and vimentin-expressing cells were well spread on collagen and exhibited numerous cell extensions enriched with filamin A and vimentin. By contrast, cells treated with small interfering RNA (siRNA) to knock down filamin A or vimentin were poorly spread; both of these cell populations exhibited >50% reductions of cell adhesion, cell surface β1 integrin expression, and β1 integrin activation. Knockdown of filamin A reduced vimentin phosphorylation and blocked recruitment of vimentin to cell extensions, whereas knockdown of filamin and/or vimentin inhibited the formation of cell extensions. Reduced vimentin phosphorylation, cell spreading, and β1 integrin surface expression, and activation were phenocopied in cells treated with the protein kinase C inhibitor bisindolylmaleimide; cell spreading was also reduced by siRNA knockdown of protein kinase C-ε. By immunoprecipitation of cell lysates and by pull-down assays using purified proteins, we found an association between filamin A and vimentin. Filamin A also associated with protein kinase C-ε, which was enriched in cell extensions. These data indicate that filamin A associates with vimentin and to protein kinase C-ε, thereby enabling vimentin phosphorylation, which is important for β1 integrin activation and cell spreading on collagen.